(untitled) - Tobin, Joseph J. (New Haven, 1992)
Colonel Sanders, Elvis, Mickey Mouse and Jack Daniels have been enthusiastically embraced by Japanese consumers. But rather than simply imitate or borrow from the West, Japanese reinterpret and transform Western products and practices to suit their culture. This book shows how in the process of domesticating foreign goods and customs, the Japanese have created a culture in which once-exotic practices (such as ballroom dancing) have become familiar, and once-familiar practices (such as public bathing) have become exotic.
Keywords: Consumers,Economic conditions; Attitudes; Japan,Japan